PENGARUH BIMBINGAN BELAJAR MAHASISWA MBKM PROGRAM KKN TEMATIK TERHADAP MOTIVASI BELAJAR ANAK DI DESA RONGGUR NIHUTA KABUPATEN SAMOSIR - Sembiring, Polintan Rehulina; Tarigan, Paska Sriulina; Raihan, Nursa Kinah (Universitas Quality, 2023)
Education is a very important tool to achieve the progress of the nation and state because good education will produce good Human Resources (HR). The world of education can be used as the basic foundation for the progress of the Indonesian nation, so the people in Ronggur Nihuta Village very well support the activities of the MBKM Student Thematic KKN Program to conduct teaching in the form of tutoring. This tutoring activity was chosen because it saw the condition of the children in Ronggur Nihuta Village who have a tendency to play mobile phones every day. Things that are done when playing on a cellphone are playing Facebook, online games and watching YouTube cartoon content. The attitude taken to deal with problems related to the future of children in Ronggur Nihuta Village, especially in the field of education. Through a heart-to-heart approach, it also slowly provides motivation to learn. MBKM Thematic KKN Program students gradually direct their mobile playing activities into learning activities in the form of tutoring. The purpose of tutoring is to assist parents in guiding their children, in addition to that so that children are able to master knowledge and can develop the skills acquired, so that by providing tutoring services it is hoped that children will be motivated in learning. Learning motivation can be interpreted as a condition that exists within an individual that encourages students to learn and carry out certain activities to get maximum learning outcomes and goals